Let Justin's age be x
Let Maggie's age be y
ATQ,
![\pmb {x = 10 + y} \\ \pmb{x-4=3(y-4)}](https://img.qammunity.org/2023/formulas/mathematics/college/1aaq933o3kke2grls2l3sjcg1iqccq9nw7.png)
Solve using the substitution method!!
- In this way the equation will be easier to solve because we will get the value of both x and y together...
![\pmb{10 + y - 4 = 3(y - 4)}](https://img.qammunity.org/2023/formulas/mathematics/college/x82uwrrvv78p4oto4up1s6lbtbuz48fuss.png)
![\sf 6 + y = 3y - 12](https://img.qammunity.org/2023/formulas/mathematics/college/igpydcp3xmgwcgkf96hypcs4w6fyzfbaxe.png)
![\sf y - 3y =- 12 - 6](https://img.qammunity.org/2023/formulas/mathematics/college/2p5e4uzg7lt12d4wxxdb3yipailkkjyky4.png)
![\sf - 2y =- 18](https://img.qammunity.org/2023/formulas/mathematics/college/fi9p3bi9fj64hhzqvy2gnujn2e86qymwx6.png)
![\sf y =9](https://img.qammunity.org/2023/formulas/mathematics/college/d7xzidzn3zycuno1ao0iw0rmhnuzphets9.png)
Substitute the value of y into the first equation
![\pmb{x= 10 + y} \\ \pmb{x = 10 + 9} \\ \pmb{x = 19}](https://img.qammunity.org/2023/formulas/mathematics/college/551s3jkan82ph7ex8gwgye9jd85xvzw8e2.png)
Thus, Maggie's age is 9 and Justin's age is 19...~